Marriage Advantage in Subjective Well-Being: Causal Effect or Unmeasured Heterogeneity?. Issue 4 (19th May 2018) - DeMaris, Alfred
ABSTRACT: I investigate whether the marriage advantage in subjective well-being is a true protective effect vs. being attributable to self-selection into (or out of) marriage based on pre-existing mental health. I utilize 1, 240 respondents from the GSS panel, a three-wave longitudinal survey collected from 2010–2014. I use a pseudo-treatment approach to informally test for the presence of self-selection. This is followed by a fixed-effect regression analysis to eliminate its influence when estimating the marriage effect. Results support the existence of self-selection: the currently married who in later waves will be exiting marriage are already more distressed than other married respondents in wave 1. And the currently not married who in later waves will be entering marriage are not more distressed in wave 1 than those remaining continuously married. A protective effect is also supported: at any given time, net of self-selection, the currently married are less distressed than the unmarried.